Unraveling atomic-scale crystallization and microstructural evolution of a selective laser melted FeCrNi medium-entropy alloy. Issue 24 (5th June 2020) - Chen, Haotian; Fang, Qihong; Zhou, Kun; Liu, Yong; Li, Jia
Abstract : Selective laser melting (SLM) provides flexibility to manufacture components with complex structures. Abstract : Selective laser melting (SLM) provides flexibility to manufacture components with complex structures. However, the unexpected crystallization and the dynamical microstructural evolution at the atomic scale still remains unknown during the SLM process. Here, the crystallization and formation mechanism of an equimolar FeCrNi medium-entropy alloy (MEA) with excellent mechanical properties prepared by SLM is studied via molecular dynamics (MD) simulations. The surface morphology, atomic microstructural evolution, and Cr elemental segregation are investigated during the crystallization process. The crystallization and microstructural characteristics are clearly observed. A large number of stacking faults take place at the boundary of the melting pool, but some stacking faults extend to the center region due to the thermal gradient effect. A segregation phenomenon of a nanoscale Cr-rich cluster occurs in the FeCrNi MEA to reveal the dynamic precipitation mechanism during the SLM process. Furthermore, higher energy density and lower scanning speed would promote the segregation and even form a mesh connected structure. The current result provides an insight into the crystallization and formation mechanism of microstructures to develop advanced alloys with high strength and toughness via the reasonable choice of SLM parameters.